The ninth step in the derivation is to find the lowest common multiple (LCM) to give [tex]x = \frac{-b\; \pm \;\sqrt{b^2 - 4ac}}{2a}[/tex]
The derivation of quadratic formula.
In Mathematics, the standard form of a quadratic equation is given by;
ax² + bx + c = 0
Mathematically, the quadratic formula is given by this equation:
[tex]x = \frac{-b\; \pm \;\sqrt{b^2 - 4ac}}{2a}[/tex]
The sixth step in the derivation is:
[tex](x + \frac{b}{2a} )^2 = \frac{b^2 - 4ac}{2a}[/tex]
The seventh step in the derivation is:
We would take the square of both sides to have;
[tex]x + \frac{b}{2a} = \frac{\sqrt{b^2 - 4ac}}{2a}[/tex]
The eigth step in the derivation is:
We would substract b/2a from both sides to have;
[tex]x = -\frac{b}{2a} \pm \frac{\sqrt{b^2 - 4ac}}{2a}[/tex]
The ninth step in the derivation is:
We would find the lowest common multiple (LCM) to have;
[tex]x = \frac{-b\; \pm \;\sqrt{b^2 - 4ac}}{2a}[/tex]
Read more on quadratic equation here: brainly.com/question/1214333
#SPJ1